Notes on some Oreste Macrì's ecdotic reflections on contemporary authors (Prassi Ecdotiche della Modernità Letteraria, 2019)
The essay aims to introduce the philological aspect (a little-studied aspect) of the rich critical personality of Oreste Macrì (1913-1998), critic with vast horizons and scholar of Italian and Spanish literature, protagonist of the Florentine hermeticism season and, then, of the cultural and critical debates of the second post-war period. Macrì can be recognized as a "philologist" in the open confrontation with Cesare Segre on the text of the Chanson de Roland, but also in the annotations to numerous critical editions of contemporary poets or in the editions he himself edited. Precisely starting from Macrì's observations on some editions and his work as an editor, the pages presented here highlight some important ecdotic reflections, in particular those that Macrì dedicates to the text-apparatus relationship in contemporary editions, to the distinction between «variante» and «variazione» in twentieth-century poetry, the need to recognize and make use of "authorial intentionality" (which concerns both writing and editorial aspects) in the preparation of an edition that is rich of unpublished works.
Keywords: Oreste Macrì; philology; literary criticism; twentieth century; variants; author's philology